PENERAPAN LKS BIOLOGI BERBASIS EKSPERIMEN UNTUK MENINGKATKAN KEMAMPUAN ILMIAH SISWA - Rohani Rohani; Agus Muliadi; Siti Nurhidayati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2018)
LKS which has been applied in schools has made students less developed scientific abilities. Worksheets that are used seem monotonous, use a colorless image, so it looks less attractive. Student worksheets are only given to be done by students, without having to guide students in solving problems contained in worksheets, and the worksheet does not contain what students have to do such as observing, analyzing, synthesizing, solving problems because there is no guidance to conduct experiments and scientific attitudes . So that makes students less able to think scientifically in learning, for that applied Experiment Based Biology Worksheet where Experiment Based Biology Worksheet can increase student activity. The purpose of this study is to apply biological worksheets to improve students' scientific abilities. This research includes Classroom Action Research (CAR) which consists of 2 cycles, each cycle has 4 stages including; planning, implementing, observing, evaluating, and reflecting. The instruments in this study were the learning implementation observation sheet (RPP) and the scientific ability test sheet. Research data were analyzed descriptively. The results of the study showed that the results of the implementation of the Learning Implementation Plan (RPP) in cycle 1 reached 75% in the good category and in cycle 2 it reached 90% in the very good category, while the students' scientific ability data in the first cycle reached 49.06 with the less scientific category , increased in second cycle reached 79.57 with the scientific category. The results of the study concluded that the application of experiment-based worksheet could improve students' scientific abilities.